El pianista - Polanski, Roman, 1933- (Barcelona Sav, 2003)
A Polish Jewish musician struggles to survive the destruction of the Warsaw ghetto of World War II.
No recomendada para menores de 13 años
Idiomas : castellano e inglés. subt. castellano, inglés
Adrien Brody, Thomas Kretschmann, Frank Finlay
Keywords: Películas cinematográficas -- DVD